Longitudinal perspectives on the psychosis spectrum in 22q11.2 deletion syndrome. Issue 10 (19th October 2017) - Tang, Sunny X.; Gur, Raquel E.
Abstract : The prevalence of psychotic disorders in individuals with 22q11.2 Deletion Syndrome (22q11DS) reaches 25–35% in young adulthood and may provide a neurogenetic model for clinical risk of psychotic disorders in the general population. This review focuses on prospective longitudinal studies in 22q11DS, which capture fluctuations in psychosis symptoms over time and may provide insights into potential demographic, clinical, cognitive, and neuroimaging predictors of psychosis‐spectrum outcomes in the general population. Findings are compared and contrasted with those from idiopathic psychosis‐spectrum populations. Onset of psychotic disorders in 22q11DS can occur over a wide range of ages, peaking in late adolescence. Symptoms may be gradually progressive or episodic in nature, highlighting the importance and challenge of risk and resilience prediction models. Converging results suggest that psychosis‐spectrum outcomes in 22q11DS are predicted by lower baseline functioning, higher baseline psychosis‐spectrum symptoms, presence of mood disturbance or anxiety, and lower baseline and subsequent decline in global measures of cognition. Predictors of transition to threshold psychotic disorders and ages of onset are similar in idiopathic clinical risk. They also share similarly global cognitive deficits, but not to the same extent as in 22q11DS. While neuroimaging studies in idiopathic clinical risk suggest loss of prefrontal gray matter, there is no consistent evidence yet emerging in the limited literature in 22q11DS. Interventional efforts in 22q11DS aimed at halting progression to psychosis or mitigating outcomes in early psychosis may be best implemented during the adolescent age range. Collaborative longitudinal efforts may help to address existing gaps in our understanding.